Integration of innovative surveying technologies for purposes of 3D documentation and valorisation of St. Herakleidios Monastery in Cyprus - Cuca, Branka; Agapiou, Athos; Kkolos, Andreas; Hadjimitsis, Diofantos G. (My University, 2014)
The integration of socio-economic aspects of heritage with innovative technologies for its documentation is progressively bringing the recording activities closer to heritage management and valorisation. This paper investigates the surveying and documentation phases of one of the most important monuments in Cyprus – the Monastery of St. Herakleidios in Politiko village, on the outskirts of the capital of Lefkosia. St. Herakleidios was the first Archbishop of Cyprus and his cult was very influential all throughout the island. With its frescos, St. Heraklideios church has inspired many byzantine artists that have decorated churches of Troodos Mountain, such as UNESCO protected Archangel Michael church and the church of Kalopanayotis village. This paper discusses the results of the survey conducted on the cave considered to be the tomb of St. Herakleidios and its church. New tendencies of surveying and modelling that could contribute to a better communication of heritage and to a more reflective society are discussed in the conclusion.
Keywords: Byzantine; Heritage documentation; Photogrammetry; Terrestrial laser scanner (TLS); Tombs